Determinant of Micro Small Medium Enterprise’s Performance: Financial Behavior as Mediating Variable - Putri, Anindita Evelyn Jessica; Sumekar, Kertati; Edris, Mochamad; Sutono, Sutono (BISNIS, 2023)
This research analyzes about financial behavior mediates the influence of financial literacy and sociodemography on the performance of micro small and medium enterprises in Kudus Regency. The population of MSMEs in Kudus is 17.184, and 175 samples were taken using purposive sampling technique. This research use Structural Equation Modeling (SEM) analyzes with AMOS24 software. The results are: Financial literacy has a significant positive effect on financial behavior, sociodemography has a significant positive effect on financial behavior, financial literacy has no effect on MSMEs performance, sociodemography has a significant positive effect on MSMEs performance, and financial behavior has no effect on MSMEs performance in Kudus Regency. Financial behavior cannot mediates the effect of financial literacy on MSMEs performances and the effect of sociodemography on MSMEs performance. These researches is provide advices to the owners of MSME especially in Kudus Regency, so they can increase their financial literacy, improve the sociodemographic’s conditions and have better financial behavior to improve MSME’s performance in Kudus.